Dietary Supplementation With Eicosapentaenoic Acid Inhibits Plasma Cell Differentiation and Attenuates Lupus Autoimmunity - Kobayashi, Azusa; Ito, Ayaka; Shirakawa, Ibuki; Tamura, Atsushi; Tomono, Susumu; Shindou, Hideo; Hedde, Per Niklas; Tanaka, Miyako; Tsuboi, Naotake; Ishimoto, Takuji; Akashi-Takamura, Sachiko; Maruyama, Shoichi; et al. (Frontiers in Immunology, 2021)
Accumulating evidence suggests that cholesterol accumulation in leukocytes is causally associated with the development of autoimmune diseases. However, the mechanism by which fatty acid composition influences autoimmune responses remains unclear. To determine whether the fatty acid composition of diet modulates leukocyte function and the development of systemic lupus erythematosus, we examined the effect of eicosapentaenoic acid (EPA) on the pathology of lupus in drug-induced and spontaneous mouse models. We found that dietary EPA supplementation ameliorated representative lupus manifestations, including autoantibody production and immunocomplex deposition in the kidneys. A combination of lipidomic and membrane dynamics analyses revealed that EPA remodels the lipid composition and fluidity of B cell membranes, thereby preventing B cell differentiation into autoantibody-producing plasma cells. These results highlight a previously unrecognized mechanism by which fatty acid composition affects B cell differentiation into autoantibody-producing plasma cells during autoimmunity, and imply that EPA supplementation may be beneficial for therapy of lupus.